Composite nano caustic soda liquid, preparation method thereof and circuit board production wastewater treatment method
By replacing traditional liquid alkali with composite nanoliquid alkali, the problem of difficulty and environmental risks in wastewater treatment of printed circuit boards is solved, and efficient and environmentally friendly wastewater treatment is achieved, reducing costs and treatment time.
Patent Information
- Application Number
- CN202510377158.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
The wastewater generated during the manufacturing process of printed circuit boards contains high COD substances such as heavy metals, acids, ammonia nitrogen, etc., which is difficult to deal with. Traditional liquid alkali is highly corrosive and volatile in treatment, and has environmental and health risks.
Compound nanoliquid alkali is used to replace traditional liquid alkali. By combining nanotechnology with liquid alkali, nanomaterials with high surface area and pore structure are formed, adsorption and catalytic activity are improved, and volatility and corrosion are reduced by optimizing components and proportions.
It quickly neutralizes the acid and alkali in wastewater, improves sewage treatment efficiency, activates the capture of metals by nanoparticles, reduces costs by 20-40%, saves treatment time by more than 40%, and is environmentally friendly and does not contain harmful chemicals.
Smart Images

Figure CN119874005A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printed circuit board production wastewater treatment, in particular to a composite nanometer liquid alkali and a preparation method thereof and a circuit board production wastewater treatment method. Background Art
[0002] The wastewater discharged by printed circuit board (PCB) manufacturing enterprises contains heavy metals, acids, ammonia nitrogen, ink and other high COD substances, which are difficult to treat. With the advancement of PCB manufacturing process technology and environmental protection treatment technology, the use of nano-alkali solution to treat PCB production wastewater can reduce the difficulty of wastewater treatment and reduce the cost of wastewater treatment. In addition, the cleaner rinse water in the process can be recycled by reverse osmosis, and the recycling rate can reach 60-80%.
[0003] Traditional liquid alkali has high corrosiveness and / or volatility in wastewater treatment, which is easy to cause harm to the environment and human health. Composite nano liquid alkali combines nanotechnology with liquid alkali, has a higher surface area and pore structure, which makes it have better activity and selectivity in fields such as adsorption and catalysis. At the same time, the lower alkalinity strength of composite nano liquid alkali can achieve milder conditions in catalytic reactions compared with traditional solid base catalysts, which helps to improve reaction selectivity and reduce the occurrence of side reactions. In addition, composite nano liquid alkali has good solubility and interfacial activity, which enables it to better interact with reactants or target substances in wastewater during catalysis and adsorption, thereby improving reaction efficiency and material conversion rate. In addition, composite nano liquid alkali also has better stability and reusability, and can maintain high catalytic activity and adsorption capacity in multiple cycles, so that it has a wider range of application capabilities and lower environmental risks. Therefore, as a new type of nanomaterial, composite nano liquid alkali has lower environmental risks and broad application prospects. Summary of the invention
[0004] The present invention provides a composite nanometer liquid alkali for treating wastewater generated in the production process of circuit boards, which can replace the traditional liquid alkali to quickly neutralize acid and alkali, improve the sewage treatment efficiency, activate the modified nanoparticles to capture metals, have high controllability, low volatility and corrosiveness, and are environmentally friendly and do not contain harmful chemicals. It not only maintains the alkalinity and solubility of traditional liquid alkali, but also improves the stability of liquid alkali, can quickly remove heavy metals, organic matter, ammonia nitrogen and other substances in wastewater, and reduce costs by 20-40%, save more than 40% of wastewater treatment time, and is simple and convenient to operate. Specifically, it includes the following technical solutions.
[0005] On the one hand, a composite nano-liquid alkali is provided, comprising the following mass concentration components: Inorganic substances 3-20g / L, Organic matter 0.5-3g / L, Nanomaterials 0.2-3g / L, Wetting agent 0.5-3g / L, Flocculant 0.2-2g / L, Accelerator 2-10g / L, Dispersant 0.1-1g / L, The mass concentration ratio of the accelerator to the dispersant is 1:(0.02-0.3); The inorganic substance is selected from at least one of sodium hydroxide, potassium hydroxide, cesium hydroxide and rubidium hydroxide; The organic substance is selected from at least one of butyl lithium, lithium diisopropylamide, benzyl lithium, and sodium tert-butoxide; The nano material is selected from at least one of nano-scale zinc chloride, silver chloride and zinc oxide; The wetting agent is selected from at least one of polyvinyl alcohol, sodium methylene dinaphthalene sulfonate, and sodium hexadecyl sulfonate; The flocculant is selected from at least one of polyaluminium chloride, polyferric sulfate, polyacrylamide and sodium aluminate; The accelerator is selected from at least one of potassium manganate, sodium manganate, and ammonium sodium manganate; The dispersant is selected from at least one of sodium allyl sulfonate, sodium propargyl sulfonate and sodium dodecylbenzene sulfonate.
[0006] Preferably, the mass concentration ratio of the inorganic substance to the organic substance is 1:(0.02-0.2).
[0007] More preferably, the mass concentration of the inorganic substance is 8-12 g / L, the mass concentration of the organic substance is 1.2-1.8 g / L; the mass concentration of the nanomaterial is 1.2-1.8 g / L; the mass concentration of the wetting agent is 1.5-2.0 g / L; the mass concentration of the flocculant is 0.8-1.2 g / L; the mass concentration of the accelerator is 5-7 g / L; and the mass concentration of the dispersant is 0.4-0.6 g / L.
[0008] More preferably, the composite nano-liquid alkali is composed of the following components in mass concentration: Inorganic substances 3-20g / L, Organic matter 0.5-3g / L, Nanomaterials 0.2-3g / L, Wetting agent 0.5-3g / L, Flocculant 0.2-2g / L, Accelerator 2-10g / L, Dispersant 0.1-1g / L, The balance is water.
[0009] The preparation method of the composite nanometer liquid alkali is as follows: inorganic substances, organic substances, nanometer materials, wetting agents, flocculants, accelerators and dispersants are added into water and mixed evenly to obtain the composite nanometer liquid alkali.
[0010] In some specific embodiments, inorganic substances, organic substances, nanomaterials, wetting agents, flocculants, accelerators, and dispersants can be added into water and stirred for 20-60 minutes to mix evenly to obtain composite nano liquid alkali.
[0011] On the other hand, a method for treating circuit board production wastewater is provided, comprising the following steps: using the above-mentioned composite nano-liquid alkali to adjust the pH of the circuit board production wastewater to 7.0-8.5.
[0012] Preferably, the temperature of the circuit board production wastewater is 25-35° C.; the amount of the composite nano-liquid alkali added to the circuit board production wastewater is 0.5-5wt%.
[0013] Furthermore, after adjusting the pH of the circuit board production wastewater to 7.0-8.5, the process further includes circulating filtration for 10-20 minutes.
[0014] Furthermore, it also includes RO reverse osmosis treatment of the wastewater after circulating filtration.
[0015] During the PCB production process, general cleaning wastewater is produced from the processes of PCB pickling and water washing after micro-etching, water washing after copper electroplating, etc. The pollutant composition is relatively simple, mainly inorganic salts. 2+ 、Ni 2+ Wastewater containing complex metal ions, various surfactants, organic acids and alkalis, such as cleaning wastewater after degreasing, neutralization and browning. Generally, the pH of washing wastewater is 2-4. The pH is adjusted to about 8.0 for coagulation and precipitation. After removing heavy metal ions, it enters the RO reverse osmosis system. The produced water can be used as production line water, and the concentrated water flows into the organic wastewater collection pool for physical, chemical and biochemical treatment.
[0016] In view of the water washing wastewater generated in the PCB production process, the present invention also provides a method for treating the water washing wastewater (PCB wastewater) using the above-mentioned composite nano-liquid alkali. The specific process flow is as follows: Figure 1 shown.
[0017] After the PCB wastewater enters the pH adjustment tank, composite nano-liquid alkali is added to adjust the pH of the wastewater to 7.0-8.5; then the wastewater enters the coagulation tank, where coagulants (such as polyaluminium chloride, polyferric sulfate, etc.) are added. The coagulant molecules form bridges between the colloidal particles and fine suspended matter in the wastewater through chemical bonds or physical adsorption, gradually forming larger flocs; then the wastewater enters the flocculation tank, where appropriate turbulent conditions are formed to allow the flocs in the wastewater to continue to grow and thicken. This process requires an appropriate degree of turbulence and sufficient residence time until a large number of flocs are finally observed to gather and slowly sink; then the wastewater enters the sedimentation tank, where the coarse flocs are preferentially deposited at the bottom of the tank, The upper water becomes clear water, and the remaining small particles continue to sink slowly and finally settle at the bottom of the pool; the wastewater after sedimentation in the sedimentation tank enters the comprehensive intermediate pool. When the wastewater passes through the comprehensive intermediate pool, part of the mud, suspended matter, etc. in the water will naturally settle down; then the wastewater is filtered through multiple media (such as quartz sand, anthracite, manganese sand), activated carbon, and two-stage ultrafilters before entering the ultrafiltration pool, and then filtered through a security filter (a precision filtration equipment, mainly used in water treatment systems or other fluid treatment systems as a pretreatment or terminal fine treatment link to protect subsequent more sophisticated or more expensive equipment from particulate matter, colloids, microorganisms and other pollutants) and filtered through an RO membrane. The produced water enters the reuse water pool and can be used as water for the production line.
[0018] Preferably, in the pH adjustment tank, the circulation filtration time is 10-20 min, the amount of nano-liquid alkali added is 0.5-5wt%, and the temperature of the wastewater solution is 25-35°C.
[0019] More preferably, in the pH adjustment tank, the circulation filtration time is 14-16 min, and the amount of nano-liquid alkali added is 2-3 wt%.
[0020] The beneficial effects of the present invention are: (1) The effective components such as inorganic substances, organic substances, nanomaterials, wetting agents, flocculants, accelerators and dispersants in the composite nano-liquid alkali of the present invention interact with each other, thereby improving the practicality of the alkali solution. The nanoparticles in the nanomaterials have extremely high specific surface area and activity, and can effectively adsorb and decompose organic matter and heavy metal ions in water, thereby achieving the purpose of quickly removing heavy metals, organic matter and ammonia nitrogen and other substances in wastewater, thereby reducing pollution to the environment; (2) The composite nano-liquid caustic soda of the present invention replaces ordinary liquid caustic soda, and the operation is simple and efficient. It can better interact with the target substance in the reactant or wastewater during the catalysis and adsorption process, thereby improving the reaction efficiency and material conversion rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0022] Figure 1 This is a process flow chart of PCB wastewater treatment according to the present invention; Figure 2 Wastewater from circuit board production; Figure 3 The solution is the circuit board production wastewater treated with the composite nano liquid alkali of Example 1; Figure 4 The solution is the circuit board production wastewater treated with the composite nano liquid alkali of Example 2; Figure 5 The solution is the circuit board production wastewater treated with the composite nano liquid alkali of Comparative Example 1; Figure 6 The solution obtained by treating the wastewater from the production of circuit boards in Comparative Example 18; Figure 7 The solution obtained by treating the wastewater from the production of circuit boards in Comparative Example 19; Figure 8 The solution obtained by treating the wastewater from the production of circuit boards in Comparative Example 22; Fig. 9 The solution obtained after the treatment of the circuit board production wastewater in Comparative Example 23; Fig.10 This is the solution after treating the circuit board production wastewater in Comparative Example 24. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0025] Example 1 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 10g / L sodium hydroxide, 1.2g / L butyl lithium, 1.2g / L zinc chloride, 1.5g / L polyvinyl alcohol, 0.8g / L polyaluminium chloride, 5g / L potassium manganate, 0.4g / L sodium allyl sulfonate, and the balance is deionized water.
[0026] Example 2 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 10 g / L potassium hydroxide, 1.2 g / L lithium diisopropylamide, 1.4 g / L silver chloride, 1.6 g / L sodium methylene dinaphthalene sulfonate, 1.0 g / L polyferric sulfate, 5.5 g / L sodium manganate, 0.5 g / L sodium propargyl sulfonate, and the balance is deionized water.
[0027] Example 3 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 12 g / L of cesium hydroxide, 1.0 g / L of benzyl lithium, 1.4 g / L of silver chloride, 1.5 g / L of polyvinyl alcohol, 0.8 g / L of polyaluminium chloride, 6 g / L of potassium manganate, 0.4 g / L of sodium allyl sulfonate, and the balance is deionized water.
[0028] Example 4 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 12g / L potassium hydroxide, 1.2g / L sodium tert-butoxide, 1.4g / L silver chloride, 1.6g / L sodium methylene dinaphthalene sulfonate, 1.0g / L polyferric sulfate, 5.5g / L sodium manganate, 0.5g / L sodium dodecylbenzene sulfonate, and the balance is deionized water.
[0029] Example 5 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 10 g / L rubidium hydroxide, 1.0 g / L benzyl lithium, 1.2 g / L silver chloride, 1.5 g / L polyvinyl alcohol, 1.0 g / L sodium aluminate, 7 g / L potassium manganate, 0.5 g / L sodium allyl sulfonate, and the balance is deionized water.
[0030] Example 6 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 10 g / L sodium hydroxide, 1.1 g / L lithium diisopropylamide, 1.2 g / L silver chloride, 1.8 g / L sodium hexadecyl sulfate, 1.0 g / L sodium aluminate, 7 g / L potassium manganate, 0.4 g / L sodium allyl sulfonate, and the balance is deionized water.
[0031] Example 7 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 8 g / L sodium hydroxide, 1.2 g / L benzyl lithium, 1.2 g / L zinc chloride, 1.5 g / L polyvinyl alcohol, 1.0 g / L polyaluminium chloride, 6 g / L sodium manganate, 0.5 g / L sodium allyl sulfonate, and the balance is deionized water.
[0032] Example 8 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 3g / L sodium hydroxide, 0.6g / L butyl lithium, 0.2g / L zinc chloride, 0.5g / L polyvinyl alcohol, 0.2g / L polyaluminium chloride, 2g / L potassium manganate, 0.6g / L sodium allyl sulfonate, and the balance is deionized water.
[0033] Example 9 The composite nano-liquid alkali of this embodiment includes the following components in mass concentration: 20g / L sodium hydroxide, 3g / L butyl lithium, 3g / L zinc chloride, 3g / L polyvinyl alcohol, 2g / L polyaluminium chloride, 10g / L potassium manganate, 1g / L sodium allyl sulfonate, and the balance is deionized water.
[0034] The composite nano-liquid alkali of Examples 1-9 was used to treat circuit board production wastewater to verify the treatment effect.
[0035] The circuit board production wastewater used in the following tests is as follows: Figure 2 The contents of various substances in the circuit board production wastewater before treatment are shown in Table 1:
[0036] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of the embodiment and stir to mix evenly, adjust the pH of the solution in the beaker to 7.0-8.5 (see Table 2 for the specific addition amount of the composite nano-liquid alkali and the solution pH), and continue stirring for 15 minutes.
[0037] After the treatment, the following tests or analyses are performed.
[0038] 1) Sedimentation rate detection: After stopping stirring, let the solution stand and record the sedimentation time for the precipitate in the solution to completely settle.
[0039] 2) COD content analysis: The absorbance of trivalent chromium (Cr³⁺) produced by the reduction of potassium dichromate is measured at a wavelength of 600±20 nm. The COD value in the sample is directly proportional to the increase in the absorbance of trivalent chromium (Cr³⁺). The absorbance of trivalent chromium (Cr³⁺) is converted into the COD value of the sample.
[0040] 3) Heavy metal content analysis: The heavy metal content is quantitatively analyzed by measuring the absorbance of the colored compounds generated by the reaction of heavy metals with color developers using UV-visible spectrophotometry.
[0041] The test results of Examples 1-9 are shown in Table 2:
[0042] It can be seen from the test results in Table 2 that the composite nano-liquid alkali provided by the present invention is used for the treatment of circuit board production wastewater, which has a rapid reaction and a fast precipitation speed and can quickly remove heavy metals, organic matter and ammonia nitrogen in the wastewater.
[0043] The solution of the circuit board production wastewater after being treated with the composite nano-liquid alkali of Example 1 is as follows Figure 3 As shown; the solution of the circuit board production wastewater after being treated with the composite nano-liquid alkali of Example 2 is as follows Figure 4 shown.
[0044] During the research process, the present invention also conducted the following exploration based on Example 1.
[0045] 1. Influence of different mass concentrations of inorganic substances The difference between the composite nano-liquid alkali of Comparative Examples 1-3 and Example 1 is that the mass concentration of the inorganic substance in the composite nano-liquid alkali is different, as shown in Table 3 for details.
[0046] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of comparative examples 1-3 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 3), and continue stirring for 15 minutes.
[0047] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 3:
[0048] As can be seen from the test results in Table 3, the composite nano-liquid alkali for treating wastewater from circuit board production does not add inorganic substances (Comparative Example 1), and the test results are not ideal. The mass concentration of inorganic substances is lower than 3g / L (Comparative Example 2) or higher than 20g / L (Comparative Example 3), and the test results are also not ideal. Therefore, the mass concentration of inorganic substances in the composite nano-liquid alkali for treating wastewater from circuit board production is preferably 3-20g / L.
[0049] The solution of the circuit board production wastewater after being treated with the composite nano-liquid alkali of Comparative Example 1 is as follows Figure 5 shown.
[0050] 2. Effects of different mass concentrations of organic matter The difference between the composite nano-liquid alkali of Comparative Examples 4-6 and Example 1 is that the mass concentration of the organic matter in the composite nano-liquid alkali is different, as shown in Table 4 for details.
[0051] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of comparative examples 4-6 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 4), and continue stirring for 15 minutes.
[0052] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 4:
[0053] As can be seen from the test results in Table 4, the composite nano-liquid alkali used for the treatment of circuit board production wastewater does not add organic matter (Comparative Example 4), the mass concentration of organic matter is lower than 0.5g / L (Comparative Example 5) or higher than 3g / L (Comparative Example 6), and the test results are not ideal. Therefore, the mass concentration of organic matter in the composite nano-liquid alkali used for the treatment of circuit board production wastewater is preferably 0.5-3g / L.
[0054] 3. Effects of different mass concentrations of nanomaterials The difference between the composite nano-liquid alkali of Comparative Examples 7-9 and Example 1 is that the mass concentration of the nano-material in the composite nano-liquid alkali is different, as shown in Table 5 for details.
[0055] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of comparative examples 7-9 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 5), and continue stirring for 15 minutes.
[0056] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 5:
[0057] From the test results in Table 5, it can be seen that the composite nano-liquid alkali used for the treatment of circuit board production wastewater does not add nanomaterials (Comparative Example 7), the mass concentration of nanomaterials is lower than 0.2g / L (Comparative Example 8) or higher than 3g / L (Comparative Example 9), and the test results are not ideal. Therefore, the mass concentration of nanomaterials in the composite nano-liquid alkali used for the treatment of circuit board production wastewater is preferably 0.2-3g / L.
[0058] 4. Effect of different mass concentrations of wetting agents The difference between the composite nano-liquid alkali of Comparative Examples 10-12 and Example 1 is that the mass concentration of the wetting agent in the composite nano-liquid alkali is different, as shown in Table 6 for details.
[0059] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of comparative examples 10-12 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 6), and continue stirring for 15 minutes.
[0060] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 6:
[0061] From the test results in Table 6, it can be seen that the composite nano-liquid alkali used for the treatment of circuit board production wastewater does not add a wetting agent (Comparative Example 10), the mass concentration of the wetting agent is lower than 0.5g / L (Comparative Example 11) or higher than 3g / L (Comparative Example 12), and the test results are not ideal. Therefore, the mass concentration of the wetting agent in the composite nano-liquid alkali used for the treatment of circuit board production wastewater is preferably 0.5-3g / L.
[0062] 5. Effect of different mass ratios of accelerator and dispersant The difference between the composite nano-liquid alkali of Comparative Examples 13 and 14 and Example 1 is that the mass concentration of the accelerator in the composite nano-liquid alkali is different, as shown in Table 7 for details.
[0063] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of Comparative Examples 13 and 14 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 7), and continue stirring for 15 minutes.
[0064] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 7:
[0065] It can be seen from the test results in Table 7 that when the proportion of the accelerator in the accelerator and the dispersant in the composite nano-liquid alkali used for the treatment of circuit board production wastewater is too small (Comparative Example 13) or too large (Comparative Example 14), the test results are not ideal. Therefore, the mass ratio of the accelerator and the dispersant in the composite nano-liquid alkali used for the treatment of circuit board production wastewater is preferably 1: (0.02-0.3).
[0066] 6. Effect of different mass concentrations of flocculants The difference between the composite nano-liquid alkali of Comparative Examples 15-17 and Example 1 is that the mass concentration of the flocculant in the composite nano-liquid alkali is different, as shown in Table 8 for details.
[0067] Treatment method: Take 500 ml of the above-mentioned circuit board production wastewater, add the composite nano-liquid alkali of comparative examples 15-17 respectively, stir and mix evenly (the specific addition amount of the composite nano-liquid alkali and the measured solution pH are shown in Table 8), and continue stirring for 15 minutes.
[0068] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 8:
[0069] From the test results in Table 8, it can be seen that no flocculant is added to the composite nano-liquid alkali for treating wastewater from circuit board production (Comparative Example 15), the mass concentration of the flocculant is lower than 0.2 g / L (Comparative Example 16) or higher than 2 g / L (Comparative Example 17), and the test results are not ideal. Therefore, the mass concentration of the flocculant in the composite nano-liquid alkali for treating wastewater from circuit board production is preferably 0.2-2 g / L.
[0070] 7. Effects of adjusting different pH values based on wastewater solution The composite nano-liquid alkali used in Comparative Examples 18-23 is the same as that in Example 1.
[0071] The difference between the treatment methods of Comparative Examples 18-23 and Example 1 is that the amount of the composite nano-liquid alkali added is different. Specifically, 500 ml of the above-mentioned circuit board production wastewater is taken, and the composite nano-liquid alkali in the amount shown in Table 9 is added and stirred to mix evenly (the pH of the solution is measured in Table 9), and stirring is continued for 15 minutes.
[0072] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 9:
[0073] It can be seen from the test results in Table 9 that when the composite nano-liquid alkali is used to adjust the pH of the circuit board production wastewater to less than 7 or greater than 8.5, the ability to treat wastewater is not obvious.
[0074] Comparative Example 18 The solution after the circuit board production wastewater treatment is as follows Figure 6 As shown; Comparative Example 19 The solution after the circuit board production wastewater treatment is as follows Figure 7 As shown; Comparative Example 22 The solution after the circuit board production wastewater treatment is as follows Figure 8 As shown; Comparative Example 23 The solution after the circuit board production wastewater treatment is as follows Fig. 9 shown.
[0075] 8. Comparative experimental test of composite nano-liquid alkali and ordinary alkali solution Comparative Example 24 uses common alkali solution (1.5wt% sodium hydroxide solution) for circuit board production wastewater treatment. Specifically, 500ml of the above circuit board production wastewater is taken, and common alkali solution is added to stir and mix evenly to adjust the pH of the wastewater solution (see Table 10 for details), and stirring is continued for 15 minutes.
[0076] After the treatment, the sedimentation rate was tested, the COD content was analyzed, and the heavy metal content was analyzed. The test results are shown in Table 10:
[0077] Comparative Example 24 The solution after the circuit board production wastewater treatment is as follows Fig.10 shown.
[0078] In summary, the composite nano liquid alkali provided by the present invention can replace traditional liquid alkali for the treatment of circuit board production wastewater, can quickly neutralize acid and alkali, improve sewage treatment efficiency, activate the modified nanoparticles to capture metals, and has high controllability, low volatility and corrosiveness; at the same time, it is environmentally friendly and does not contain harmful chemicals. It not only maintains the alkalinity and solubility of traditional liquid alkali, but also improves the stability of liquid alkali, and can quickly remove heavy metals, organic matter, ammonia nitrogen and other substances in wastewater, while reducing costs by 20-40%, saving time by more than 40%, and being simple and convenient to operate.
[0079] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A composite nano-liquid alkali, characterized in that: Includes the following mass concentration components: Inorganic substances 3-20g / L, Organic matter 0.5-3g / L, Nanomaterials 0.2-3g / L, Wetting agent 0.5-3g / L, Flocculant 0.2-2g / L, Accelerator 2-10g / L, Dispersant 0.1-1g / L, The mass concentration ratio of the accelerator to the dispersant is 1:(0.02-0.3); The inorganic substance is selected from at least one of sodium hydroxide, potassium hydroxide, cesium hydroxide and rubidium hydroxide; The organic substance is selected from at least one of butyl lithium, lithium diisopropylamide, benzyl lithium, and sodium tert-butoxide; The nano material is selected from at least one of nano-scale zinc chloride, silver chloride and zinc oxide; The wetting agent is selected from at least one of polyvinyl alcohol, sodium methylene dinaphthalene sulfonate, and sodium hexadecyl sulfonate; The flocculant is selected from at least one of polyaluminium chloride, polyferric sulfate, polyacrylamide and sodium aluminate; The accelerator is selected from at least one of potassium manganate, sodium manganate, and ammonium sodium manganate; The dispersant is selected from at least one of sodium allyl sulfonate, sodium propargyl sulfonate and sodium dodecylbenzene sulfonate.
2. The composite nano-liquid alkali according to claim 1, characterized in that: The mass concentration ratio of the inorganic substance to the organic substance is 1:(0.02-0.2).
3. The composite nano-liquid alkali according to claim 1, characterized in that: The mass concentration of the inorganic substance is 8-12 g / L, and the mass concentration of the organic substance is 1.2-1.8 g / L.
4. The composite nano-liquid alkali according to claim 1, characterized in that: It is composed of the following components in mass concentration: Inorganic substances 3-20g / L, Organic matter 0.5-3g / L, Nanomaterials 0.2-3g / L, Wetting agent 0.5-3g / L, Flocculant 0.2-2g / L, Accelerator 2-10g / L, Dispersant 0.1-1g / L, The balance is water.
5. The method for preparing the composite nano-liquid alkali according to any one of claims 1 to 4, characterized in that: Inorganic substances, organic substances, nanometer materials, wetting agents, flocculants, accelerators and dispersants are added into water and mixed evenly to obtain composite nanometer liquid alkali.
6. A method for treating wastewater from circuit board production, characterized in that: The method comprises the following steps: using the composite nano-liquid alkali described in any one of claims 1 to 5 to adjust the pH value of the circuit board production wastewater to 7.0-8.
5.
7. The method for treating circuit board production wastewater according to claim 6, characterized in that: The temperature of the circuit board production wastewater is 25-35°C.
8. The method for treating circuit board production wastewater according to claim 6, characterized in that: The amount of the composite nano-liquid alkali added to the circuit board production wastewater is 0.5-5wt%.
9. The method for treating circuit board production wastewater according to claim 6, characterized in that: After adjusting the pH of the circuit board production wastewater to 7.0-8.5, the method further includes circulating filtration for 10-20 minutes.
10. The method for treating circuit board production wastewater according to claim 9, characterized in that: It also includes RO reverse osmosis treatment of the wastewater after circulating filtration.
Citation Information
Patent Citations
Method for preparing oxidation catalyst from gold ore tailing slag, and prepared oxidation catalyst and application thereof
CN102580743A
Polymerization titanium salt modified chitosan flocculating agent, and preparation method and application thereof
CN106517464A
Porous nanocomposite polymers for water treatment
CN106660839A
Sludge deodorant for municipal sewage treatment plants
CN111892261A
Heavy metal wastewater adsorbent and preparation method thereof
CN112774648A
Cited By
Alkaline medium-coarsening micro-etching liquid and preparation method and micro-etching method thereof
CN120738649A
Alkaline middle and rough etching micro-etching solution, preparation method and micro-etching method thereof
CN120738649B